Farm Budgets : from farm income analysis to Agricultural Project Alalysis. - "Brown , Maxwell L." (Baltimore, 1979)
There is a wealth of literature on farm income analysis an agricultural project analysis, but little has been published which clarifies the difference between them or which shows how the transition is made from one to the other. The purpose of this study is to bridge this gap, providing theoretical instruction in layman's language and giving practical guidance to those responsible for planning or making investment decisions in agriculture or in the wider field or rural development.
Keywords: Budgets .